First language interference in writing proficiency in Indonesian as a third language for foreign speakers - Ardiansyah, Roely; Harjanti, Fransisca Dwi (BAHASTRA, 2025)
This study aims to explore first language interference in the writing proficiency of foreign speakers learning Indonesian as their third language. The research data consist of Indonesian sentences influenced by the first language of foreign speakers, namely Mandarin and Spanish. The participants are two international students from different countries, both female, studying at higher education institutions in Indonesia. This qualitative study collected data through Indonesian writing tests. Content analysis was employed to identify patterns of first language interference at syntactic and lexical levels in their Indonesian writing. The findings reveal: (1) syntactic interference from Spanish (L1) and English (L2) to Indonesian (L3) significantly impacts sentence structures and language elements; (2) syntactic interference from Mandarin (L1) and English (L2) shows different impacts on Indonesian (L3) structure and usage.